Effects of Aloe vera Gel on Osteoclast and Osteoblast Activity and Receptor Activator of Nuclear Factor Kappa-B Ligand Expression During Bone Remodeling Following Orthodontic Temporary Anchorage Device Placement: An In Vivo Study - Siregar, Pepi Riyani (2026)
The biomedical use of Aloe vera continues to expand, including in orthodontics where its role in bone remodeling is of particular interest. This study aimed to evaluate the effect of Aloe vera gel on osteoclast, osteoblast, and RANKL expression following Temporary Anchorage Device (TAD) placement. Thirty male New Zealand White rabbits were randomly assigned to control and treatment groups. TADs were placed in the maxillary buccal region, and the treatment group received 50% Aloe vera gel topically.  Each rabbit in the treatment group received 0.5 g of 50% Aloe vera gel topically around the TAD site twice daily. Histological analysis and ELISA were conducted on days 3, 7, and 14. The results showed a significant increase in osteoblast counts on days 7 and 14 (p<0.05). Osteoclast counts remained elevated on day 3 but were significantly lower than the control group (p < 0.05), followed by a further decrease on day 14. RANKL expression increased moderately over time (R²=0.517). Regression analysis demonstrated a time-dependent effect of Aloe vera on osteoblasts (R²=0.834) and osteoclasts (R²=0.928). These findings suggest that Aloe vera gel supports bone remodeling by relatively suppressing osteoclast activity, enhancing osteoblast response, and modulating RANKL expression proportionally, making it a promising adjunct for improving TAD stability in clinical orthodontics.